Advancements and Challenges in Paper-Based Diagnostic Devices for Low-Resource Settings: A Comprehensive Review on Applications, Limitations, and Future Prospects - Gayatri, Alluri Pavani; Bandaru, Naga Raju; Bonthu, Mohan Gandhi; Tandu, Divya Sree (Current Biotechnology, 2025)
Paper-Based Diagnostic Devices (PBDDs) represent a breakthrough in affordable, rapid, and point-of-care diagnostics, particularly in low-resource settings. These devices utilize simple materials such as paper combined with microfluidics and colorimetric or electrochemical detection methods to provide accessible and cost-effective diagnostic solutions for a wide range of diseases. This review explores the development, applications, and advancements of PBDDs in various disease categories, including cardiovascular diseases, infectious diseases, cancer, neurological and psychological disorders, and other chronic conditions. The paper highlights the challenges PBDDs face, including issues related to sensitivity, specificity, and scalability, while also examining their future prospects driven by advances in nanotechnology, digital integration, and manufacturing techniques. As technological innovations continue to improve the sensitivity, multiplexing capabilities, and digital connectivity of PBDDs, their potential to transform healthcare delivery, especially in underserved areas, becomes even more significant. This review also discusses the regulatory, environmental, and operational challenges PBDDs encounter and suggests potential solutions that could support their wider adoption. The future of PBDDs lies in overcoming current limitations and leveraging their advantages in low-resource environments, with the goal of expanding access to high-quality diagnostics globally.
Keywords: PBDDs